Facile Metal Coordination of Active Site Imprinted Nitrogen Doped Carbons for the Conservative Preparation of Non‐Noble Metal Oxygen Reduction Electrocatalysts. Issue 9 (18th December 2017) - Mehmood, Asad; Pampel, Jonas; Ali, Ghulam; Ha, Heung Yong; Ruiz‐Zepeda, Francisco; Fellinger, Tim‐Patrick
Abstract: Iron‐ or cobalt‐coordinated heteroatom doped carbons are promising alternatives for Pt‐based cathode catalysts in polymer‐electrolyte fuel cells. Currently, these catalysts are obtained at high temperatures. The reaction conditions complicate the selective and concentrated formation of metal–nitrogen active sites. Herein a mild procedure is introduced, which is conservative toward the carbon support and leads to active‐site formation at low temperatures in a wet‐chemical metal‐coordination step. Active‐site imprinted nitrogen doped carbons are synthesized via ionothermal carbonization employing Lewis‐acidic Mg 2+ salt. The obtained carbons with large tubular porosity and imprinted N4 sites lead to very active catalysts with a half‐wave potential ( E 1/2 ) of up to 0.76 V versus RHE in acidic electrolyte after coordination with iron. The catalyst shows 4e − selectivity and exceptional stability with a half‐wave potential shift of only 5 mV after 1000 cycles. The X‐ray absorption fine structure as well as the X‐ray absorption near edge structure profiles of the most active catalyst closely match that of iron(II)phthalocyanine, proving the formation of active and stable FeN4 sites at 80 °C. Metal‐coordination with other transition metals reveals that Zn–N x sites are inactive, while cobalt gives rise to a strong performance increase even at very low concentrations. Abstract : Nonprecious metal electrocatalysts consisting of transition iron–nitrogen (FeN x ) active sites present a promising substitute for platinum‐based oxygen reduction electrocatalysts. This study introduces a novel approach for synthesizing highly active and stable FeN4 sites by simple low temperature metal‐coordination (metalation or transmetalation) of active site imprinted nitrogen doped carbons, fully preventing the formation of other undesired metal phases.